2010
DOI: 10.1097/jpn.0b013e3181db5377
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Chilean Mothers to Massage Their Full-Term Infants

Abstract: The purpose of this study was to evaluate the effects of massage on infant weight gain and exclusive maternal breast-feeding of an intervention that involved teaching mothers to massage their full-term infants. The sample included 100 healthy newborn infants who were receiving primary healthcare at 3 health centers in a low-income neighborhood of Santiago, Chile. The control group included 65 infants and the massage group included 35 infants. During their second well-child clinic visit, clinic nurses provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Another study in Chile assessed infant massage provided by mothers as another way to have skin-to-skin stimulation and reported improvements in early weight gain, but no improvements in later weight gain (Serrano, Doren, & Wilson, 2010). …”
Section: Developmental Periods: Perinatal Infant/toddler Young Childmentioning
confidence: 99%
“…Another study in Chile assessed infant massage provided by mothers as another way to have skin-to-skin stimulation and reported improvements in early weight gain, but no improvements in later weight gain (Serrano, Doren, & Wilson, 2010). …”
Section: Developmental Periods: Perinatal Infant/toddler Young Childmentioning
confidence: 99%
“…Also, Roosbahani and Narenji compared the effects of massaging with sesame oil with no massaging on term infants, and found no statistically significant difference between the groups [21]. In this study, no relationship was found between infant weight (height) gain and gender likewise [5] [18] [31].…”
Section: Discussionmentioning
confidence: 78%
“…However, the difference of average height increase between the participants of sesame oil and sunflower oil groups was not statistically significant. According to Soriano et al, significant height gain was observed in preterm infants after 30 days of oil massage [5]. Agarwal et al, reported significant increase in height among term infants after a 6 week massage [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations